2012
DOI: 10.14411/fp.2012.035
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection affects cognitive function - corrigendum

Abstract: 253In the recent issue of Folia Parasitologica (59: 93-98), Guenter et al. (2012) published results of a study showing that the effect of latent toxoplasmosis on cognitive function of 70 subjects cannot be proved to exist using a panel of five neuropsychological tests (Guenter et al. 2012). It must be mentioned that the data (mostly ordinal variables without normal distribution) were analysed either with parametric tests (GLM) or with more proper nonparametric tests, but without controlling for age and sex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
1
14
1
Order By: Relevance
“…In that study, Toxoplasma gondii seropositivity was associated with better action control, which the authors speculated might have been due to changes in dopamine transmission related to Toxoplasma gondii seropositivity [31]. Finally, one other study found some evidence of better performance in participants positive for Toxoplasma gondii on some but not all cognitive tests administered [32]. While unexpected, our finding of an association between Toxoplasma gondii serointensity and better reaction time comes from a sample size of 6,752, a large sample that minimizes the chance for error due to small sample.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 82%
“…In that study, Toxoplasma gondii seropositivity was associated with better action control, which the authors speculated might have been due to changes in dopamine transmission related to Toxoplasma gondii seropositivity [31]. Finally, one other study found some evidence of better performance in participants positive for Toxoplasma gondii on some but not all cognitive tests administered [32]. While unexpected, our finding of an association between Toxoplasma gondii serointensity and better reaction time comes from a sample size of 6,752, a large sample that minimizes the chance for error due to small sample.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 82%
“…Previous studies reports have been contradictory results, with some investigators reporting impaired function (Gajewski, Falkenstein, Hengstler, & Golka, 2014) , while others did not detect statistically significant effects (Guenter et al, 2012) & Kruszonet al 2014) , (J. Flegr et al, 2012) (Pearce, Kruszon-Moran, & Jones, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Others have suggested that the associations are stronger in men, possibly due to hormonal effects (J. Flegr et al, 2012) (J. Flegr et al, 2012; J.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though many studies suggest seropositivity for latent toxoplasmosis is associated with worse outcome, whether it be cognitive or psychiatric, other studies suggest that seropositivity may not be purely detrimental. For example, Flegr et al (2012) analyzed males and females separately and found that while seropositive females did more poorly on one of several cognitive measures compared to seronegative females, seropositive males did equally well on most cognitive measures and actually did better than seronegative males on two of the cognitive measures. Similarly, Stock et al (2014) found that seropositivity for T. gondii was associated with better performance on a measure of action control.…”
Section: Discussionmentioning
confidence: 99%